Problems with applying human rights in the actions of public administration - Puczko, Aleksandra (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2022)
This article aims to analyze the contemporary problem of respecting human rights in the actions of public administration. To that end, it aims to show the causes of the issue in question and propose solutions. The article opens with a description of the legal aspect of human rights from the general perspective as a matter of rules and elements of the legal system. This part of the article presents the legal grounds for and obstacles to incorporating human rights and the acts that regulate them into the actions of public administration. In the subsequent sections, the analysis shifts to a detailed perspective. The first one concerns the reliance of the public administration’s actions on Art. 6 point 1 of the European Convention on Human Rights and shows the issues with applying it to administrative cases, as noted in the literature and jurisprudence. The second addresses the issues associated with incorporating human rights regulations into the application of the substantial law. This problem is analyzed from the standpoint of legal regulations, values and interpretation. At the same time, the article aims to show that while on the one hand public administration is responsible for safeguarding rights, on the other it is also entitled to breach and limit.